Legal Regulation of Platform Employment in Kazakhstan: Classification of Labour Relations and Liability of Digital Platforms (VERITAS LEGIS JOURNAL, 2025)
The article examines platform employment in the Republic of Kazakhstan in the context of rapid digitalisation and the expansion of the platform economy. It is argued that new forms of interaction between digital platforms and service providers transform traditional employment models and generate legal uncertainty regarding workers’ status and the allocation of liability. Using a comparative legal method, the study analyses regulatory approaches and court practice in the European Union, the United States, and selected European jurisdictions. Particular attention is paid to ride-hailing platforms and the absence of a statutory definition of a “taxi aggregator”, which allows platforms to present themselves as mere intermediaries and to limit their civil liability. The article reviews judicial trends in the gig economy that qualify platform-based arrangements as employment relationships based on their factual characteristics. In addition, the paper discusses Kazakhstan’s case law, including Ospan A.A. v. Glovo Kazakhstan LLP, which supports the need to assess the substance of the relationship rather than its formal contractual label. The study concludes that Kazakhstan should further develop its legal framework to strengthen worker and consumer protection, increase platform accountability for providers’ actions, and ensure compliance with safety and service quality standards.
Keywords: platform employment; digital platforms; taxi aggregators; gig economy; employment relationship; civil liability; case law; consumer protection